Promising Male Hormonal Contraceptive are Well Established Soon a Reality - Gunardi, Eka R; Soetarso, Arnold; Addina, Putri (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To understand the modalities used for male hormonal contraception. Methods: Literature review Conclusion: Male contraceptive methods are still limited but hormonal contraceptive methods are being developed. The basic mechanism of male hormonal contraception is to inhibit spermatogenesis by suppression of the hypothalamic-pituitary-testicular axis function. Administration of testosterone or androgen derivative that is given in combination with progestin or GnRH antagonist shows that male hormonal contraceptive is reversible, effective, and acceptable as a male contraceptive method. However, no method of male hormonal contraceptive is ready for clinical use and marketed due to limited studies. [Indones J Obstet Gynecol 2015; 3-4: 239-243] Keywords: GnRH antagonist, male hormonal contraceptive, progestin, testosterone